2011
DOI: 10.1111/j.1365-3016.2011.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis investigating breast feeding and childhood wheezing illness

Abstract: There is conflicting evidence concerning the relationship between breast feeding and wheezing illness. The objective of this study was to investigate whether there is any association between breast feeding and wheezing in children aged over 5 years and to discover possible sources of heterogeneity. An electronic search of MEDLINE and EMBASE databases was conducted from January 2000 to June 2010. In addition, reference lists from relevant publications were searched. Birth cohort, cross-sectional and case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 77 publications
0
55
0
3
Order By: Relevance
“…Previous studies examining the protective effect of breastfeeding on asthma at older ages showed conflicting results. Some studies observed that breastfeeding was associated with a decreased risk of asthma,3 4 and others did not,5 6 or saw even an increased risk of asthma in school-aged children and adulthood 7 8. Also, the increased protective effect of breastfeeding on asthma in atopic children remains debatable as earlier studies, including a recent meta-analysis, observed more or less protective effects of breastfeeding on asthma in school-aged atopic children or children with a family history of asthma 6–8.…”
Section: Commentarymentioning
confidence: 99%
“…Previous studies examining the protective effect of breastfeeding on asthma at older ages showed conflicting results. Some studies observed that breastfeeding was associated with a decreased risk of asthma,3 4 and others did not,5 6 or saw even an increased risk of asthma in school-aged children and adulthood 7 8. Also, the increased protective effect of breastfeeding on asthma in atopic children remains debatable as earlier studies, including a recent meta-analysis, observed more or less protective effects of breastfeeding on asthma in school-aged atopic children or children with a family history of asthma 6–8.…”
Section: Commentarymentioning
confidence: 99%
“…Some studies have found either no or an increased risk of asthma with breastfeeding (2022). These inconsistencies may be due to differences in phenotypes and related to the age of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we have a sample rich in covariate information linked to birth certificate data for multivariate adjustment, including detailed duration of exclusive breastfeeding, daycare attendance, parental atopy, pets, and child bronchitis/cold and flu history. These latter covariates allowed us to explore the hypothesis that the benefits from breastfeeding might be due to a reduction in virus-associated wheeze (9,22). However, including both bronchitis and severe cold/flu prior to one year in our models did not change the estimate for breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…A review that included all study types published in 2011 considering breastfeeding and wheezing illness beyond 5 years of age only showed no association, highlighting an enormous controversy in this area [27] . The authors of this review recommend that further studies should aim to be of the highest quality and specific diagnostic criteria for asthma to be included.…”
Section: Systematic Reviewsmentioning
confidence: 99%